(untitled) (Al-Academy, 2021)
Psychological aspects are a major influence and motivation factor in many cinematic and television works such as television series. There are many films that dealt with psychological issues through the personality affected by psychological projections and complexes that lead towards abnormal behavior and actions in most cases, so the researchers chose the title and the research problem was raised through the following question: What is the mechanism that fulfills a psychological role in the narrative film? The objectives of the research were to reveal the mechanism used to instill psychological contents in the feature film? As for the limits of the research, it was an intentional sample, and the researchers adopted the descriptive analytical approach to the content. All cinematic, television and even dramatic works, as the researchers discovered that the psychological aspect of any dramatic work is enshrined in most of the elements of the cinematic medium